2017
DOI: 10.1002/2016gl072035
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric variability contributed to and sustained the recent hiatus in Eurasian winter warming

Abstract: The recent hiatus in global‐mean surface temperature warming was characterized by a Eurasian winter cooling trend, and the cause(s) for this cooling is unclear. Here we show that the observed hiatus in Eurasian warming was associated with a recent trend toward weakened stratospheric polar vortices. Specifically, by calculating the change in Eurasian surface air temperature associated with a given vortex weakening, we demonstrate that the recent trend toward weakened polar vortices reduced the anticipated Euras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 54 publications
5
86
1
Order By: Relevance
“…Although clarifying the causes of the vertical coupling intensity is beyond our scope, the obtained results suggest that WPV events occurring in light‐ice years over the BKS tend to strongly affect tropospheric circulation and midlatitude surface temperature. This is consistent with the results of Garfinkel et al () and Kretschmer et al (), showing that a recent low temperature anomaly over Eurasia in winter was preceded by stratospheric polar vortex weakening.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although clarifying the causes of the vertical coupling intensity is beyond our scope, the obtained results suggest that WPV events occurring in light‐ice years over the BKS tend to strongly affect tropospheric circulation and midlatitude surface temperature. This is consistent with the results of Garfinkel et al () and Kretschmer et al (), showing that a recent low temperature anomaly over Eurasia in winter was preceded by stratospheric polar vortex weakening.…”
Section: Resultssupporting
confidence: 93%
“…This Eurasian surface temperature signals are also apparent in horizontal maps averaged 30 days after Day 0 (Figures b and d). These results suggest that the recent Eurasian cold conditions (Cohen et al, ; Garfinkel et al, ) were partly related to stronger vertical coupling of the WPV events modulated by sea‐ice loss. A question remains about the mechanisms of the stronger vertical coupling.…”
Section: Discussionmentioning
confidence: 75%
“…Seviour (2017) examined large ensembles of coupled climate model simulations and concluded that the forced response of the vortex was small relative to internal variability, and that vortex trends of similar magnitude to those observed can be generated purely by internal climate variability [43]. The latter conclusion was also reached by Garfinkel et al (2017), who found no consistent change in the strength of the polar vortex in model simulations forced with observed GHG concentrations, sea surface temperatures and sea ice [42]. However, unforced internal variability was sufficiently strong that some individual ensemble members reproduced the observed polar vortex weakening.…”
Section: The Arcticmentioning
confidence: 92%
“…In particular, the occurrence of sudden stratospheric warming (SSW) events favours negative NAO phases that are often associated with cold extremes over Eurasia. It has been shown that during periods with a weak stratospheric polar vortex, extremely low temperatures over northern Europe are more likely (Kidston et al ., ) and longer lasting (Garfinkel et al ., ). These studies reinforce the hypothesis that the state of the stratospheric polar vortex may be important for the evolution, intensity and – in particular – the persistence of surface cold anomalies.…”
Section: Introductionmentioning
confidence: 99%